PENDEKATAN LINGUISTIK DALAM PENAFSIRAN AL-QUR'AN - Abdullah Mu'afa (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2012)
Linguistic concept is a part of theory or the way to interpret Qur'an but it is still fuzzy. So, position the linguistic interpretation in this study is very important. In this case, attempting of systematize theories are used in the interpretation of the linguistic to position in the place that is found the exact meaning. From the result of the study is found that the linguistic position is in the realm of Qur'an interpretation can be seen from two aspects, namely language is as the language of the methodological and as theological argument. The first meaning it is presupposes that the language is usually manifest in the rules and theories. And the second, language is manifest a code of values that is ​ fought by al- Qur’an. The language of the Qur'an is sacred code system God, holy and sublime, human or system code of profane, historical, and cultural. isn’t it?